2019
DOI: 10.1371/journal.pone.0225717
|View full text |Cite
|
Sign up to set email alerts
|

The relation between circulating levels of vitamin D and parathyroid hormone in children and adolescents with overweight or obesity: Quest for a threshold

Abstract: The level of serum 25-hydroxyvitamin D (25(OH)D) at which intact parathyroid hormone (iPTH) is maximally suppressed (suppression point) and below which PTH begins to rise (inflection point) has been used to define optimum 25(OH)D concentration. We aimed to study the association of circulating iPTH with 25(OH)D concentrations and to determine a 25(OH)D threshold associated with a significant iPTH suppression. This cross-sectional study was conducted on 198 boys and 180 girls, aged 6–13 years with BMI ≥ 1SD (WHO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Although serum calcium and phosphate level were low in the CG, they were still within the normal range. Several investigators found a balanced level of Ca and P in spite of low levels of vitamin D 3, due to the higher level of parathyroid hormone which stimulates calcium and phosphate reabsorption from kidneys [ 39 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although serum calcium and phosphate level were low in the CG, they were still within the normal range. Several investigators found a balanced level of Ca and P in spite of low levels of vitamin D 3, due to the higher level of parathyroid hormone which stimulates calcium and phosphate reabsorption from kidneys [ 39 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…While vitamin D will function to help balance calcium in the blood when parathyroid hormone has converted vitamin D into a hormonal form of vitamin D in the kidneys. 31 • 32 .…”
Section: Effects Of Vitamin D Supplementation On Biochemical Results Concentration Of Serum 25 (Oh) D and Serum Calciummentioning
confidence: 99%
“…Esmaili et al pointed out that a higher level of 25(OH)D of 30 ng/mL was a risky inflection point [18]. Other studies set up suitable VitD levels for overweight/obesity or metabolism disorder in children on the basis of their study population, and inflection values varied, ranging from 10 ng/mL to 32 ng/mL [44,45]. In one review, the authors recommended maintaining serum 25(OH)D levels >30 ng/mL in pediatrics to prevent VitD deficiency, thus avoiding the risk of both skeletal and extraskeletal diseases [46].…”
Section: Discussionmentioning
confidence: 99%